Studi Awal Geologi di Wilayah Kabupaten Pamekasan untuk Mendukung Pemilihan Calon Tapak Instalasi Desalinasi Nuklir - Ngadenin, Ngadenin; Subiantoro, Lilik; Widana, Kurnia Setiawan (EKSPLORIUM, 2014)
The area around the southern coast Pamekasan is one of the candidates for the alternatives location of nuclear desalination plant site. In 1949 around Sampang Madura ever tectonic earthquake measuring 5 on the Richter scale with its epicenter on land. Tectonic earthquake with epicenter on land is likely related to the presence of active faults on the island of Madura. Location prospective nuclear desalination plant site should be away or free of active faults. Aim of this study is to obtain geological information and know the characteristics of tectonics including active fault to support site studies of nuclear desalination plant on the island of Madura. The method used is the geological mapping scale, 1 : 50,000. Lithology in the area along the south coast district Pamekasan is alluvium Holocene age and conglomerate units of Pleistocene age. There were no indications of active faults in the region. Candidates site at this location is less attractive in terms of geotechnical foundation as can be ascertained bedrock will be found sufficient in that building construction will require expensive.